An extended account of contract monitoring strategies as patterns of communication. (7th March 2018) - SWORDS, CAMERON; SABRY, AMR; TOBIN-HOCHSTADT, SAM
Abstract: Contract systems have come to play a vital role in many aspects of software engineering. This has resulted in a wide variety of approaches to enforcing contracts—ranging from the straightforward pre-condition and post-condition checking of Eiffel to lazy, optional, and parallel enforcement strategies. Each of these approaches has its merits, but each has required ground-up development of an entire contract monitoring system. We present a unified approach to understanding this variety, while also opening the door to as-yet-undiscovered strategies. By observing that contracts are fundamentally about communication between a program and a monitor, we reframe contract checking as communication between concurrent processes. This brings out the underlying relations between widely studied enforcement strategies, including strict and lazy enforcement as well as concurrent approaches, including new contracts and strategies. We show how each of these can be embedded into a core calculus, and demonstrate a proof (via simulation) of correctness for one such encoding. Finally, we show that our approach suggests new monitoring approaches and contracts not previously expressible.